2017
DOI: 10.1002/2016jb013551
|View full text |Cite
|
Sign up to set email alerts
|

Upper mantle discontinuity structure beneath eastern and southeastern Tibet: New constraints on the Tengchong intraplate volcano and signatures of detached lithosphere under the western Yangtze Craton

Abstract: We present new constraints on the upper mantle transition zone structure beneath eastern and southeastern Tibet based on P wave receiver functions for a large broadband data set from two very dense seismic arrays. A clear depression of both the 410 km and 660 km discontinuities is detected west of the Red River fault relative to the east. The correlated topographic variations across the Red River fault are indicative of temperature changes in the upper mantle above the transition zone, which suggests that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…A numerical simulation study suggests that this upwelling is part of a return flow system induced by actively sinking slab segments and is capable of producing decompression melting in the upper mantle [ Faccenna et al , ]. A similar mechanism is involved in a recent RF study to explain low upper mantle velocities and Cenozoic volcanism in southwestern China, directly to the north of our study area [ Zhang et al , ].…”
Section: Discussionmentioning
confidence: 63%
“…A numerical simulation study suggests that this upwelling is part of a return flow system induced by actively sinking slab segments and is capable of producing decompression melting in the upper mantle [ Faccenna et al , ]. A similar mechanism is involved in a recent RF study to explain low upper mantle velocities and Cenozoic volcanism in southwestern China, directly to the north of our study area [ Zhang et al , ].…”
Section: Discussionmentioning
confidence: 63%
“…One mechanism suggests that the Tengchong volcano is directly driven by the active subduction of the Indian plate, resulting from slab dehydration and induced mantle convection, like many volcanoes in subduction zones as well as the Changbai intraplate volcano in northeast China (Huang et al, , Huang, Wang, Xu, Wang, et al, ; Lei et al, , ; Zhao & Tian, ; Lei & Zhao, ). Another mechanism argues for the contribution of mantle flow from beneath the subducting Indian slab (Zhang et al, ); a slab window created by slab break‐off is necessary in this case. However, the present results show a continuous Indian slab in the upper mantle (Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…Beneath the eastern Himalayan syntaxis and Burma, high‐velocity bodies, with active seismicity in the top 200‐km depth (Engdahl et al, ; Ni et al, ), extend down to 400‐km depth (Huang, Zhao, et al, ; Li et al, ; Pesicek et al, ; Wei et al, ), representing the subducting Indian plate. The depressed 660‐km velocity discontinuity (D660) implies that cold material has probably sunk into the mantle transition zone (MTZ; Xu et al, ; Yu et al, ; Zhang et al, ). Beneath the Sichuan basin, the core of the stable Yangtze craton, high‐velocity anomalies are also predominant in the upper mantle (Huang & Zhao, ; Huang, Wang, Xu, Wang, et al, ; Lei & Zhao, ; Tao et al, ; Wei et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of plate tectonic reconstructions, Neo‐Tethyan Oceanic crust was subducted into the mantle beneath Tengchong in the Cretaceous (Hafkenscheid et al, ; Van der Voo et al, ). Recently, high‐resolution seismic and tomographic data showed that a broad low‐velocity zone extends down to the 410 km discontinuity with a high‐velocity anomaly region at ~660 km (e.g., Lei et al, , ; R. Zhang et al, ; Wei et al, ). The high‐velocity region might represent a cold and stagnant slab, probably the Neo‐Tethyan Oceanic slab (Figure ; Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%